Health Professionals' Knowledge and Attitudes toward NSSI in USA and Belgium - Prosser, Emily C.; Quigley, Katherine E. (My University, 2012)
Studies have documented the presence of non-suicidal self-injury (NSSI) in numerous countries (e.g., Jeffrey & Warm, 2002; Heath et al., 2006; Plener et al., 2008). Little research has explored the attitudes of those in the mental health professions (i.e., counselors, psychologists). The goal of this study was to cross-culturally examine the attitudes of mental health professionals toward individuals who self-injure and identify differences and similarities between the United States and Belgium.
Color poster with text and graphs.
Keywords: Mental health personnel--Training of--Belgium; Mental health personnel--Training of--United States; Mental health personnel--United States--Attitudes; Mental health personnel--Belgium--Attitudes; Self mutilation; Posters